Who should teach? A Chinese teacher candidate's understandings of a good teacher and racialised experiences. Issue 2 (15th March 2018) - Maddamsetti, Jihea (Kang); Flennaugh, Terry K.; Rosaen, Cheryl L.
ABSTRACT: Being a good teacher depends on many cultural and linguistic assumptions. Dominant definitions of a good teacher are often based on these implicit assumptions. Probing notions of a good teacher, we examine the endeavors of a Chinese international pre-service teacher, Ling, to become a "good teacher" through her encounters with micro-aggression in the context of her coursework and fieldwork at a U.S. university. The data presented here were collected through semi-structured interviews and field notes from 2014 to 2015 as part of a larger ethnographic case study. We find that the process of becoming a good teacher depends on many cultural and linguistic assumptions that are linked to micro-aggression. We conclude by reflecting on Ling's understanding of a good teacher in light of dominant views on the matter and her ambivalence to speak up, and make recommendations for further research to allow for alternative views of good teachers to coexist.